Simultaneous Estimation of Pregabalin and Etoricoxib using Novel HPLC Method: An Application in Quantitative Analysis of Pharmaceutical Dosage Forms - Chaudhary, Amit; Singh, Bhuvnesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: A new optimised method was developed for simultaneous estimation of new FDA approved drugs using RP-HPLC method that would emphasize the use of these drugs in various industries for quality measurements. Objectives: The objective of the present study to develop and validate a new simple, novel, precise, rapid, reliable, accurate and reproducible reverse-phase high-performance liquid chromatography (RP-HPLC) technique for simultaneous estimation of Pregabalin (PREG) and Etoricoxib (ETOR) in bulk and formulation. Materials and Mehtods: This separation was done by using a mixture of methanol: acetonitrile: phosphate buffer (pH 5) at the ratio of (40:20:20) as mobile phase, with a hypersil ODS, C18 (250 mm × 4.6 mm, i.d.2.5 µm). The flow rate was 1.0 ml min-1 and effluents were monitored at 215 nm by using UV-visible detector with injection volume was 20 μl. Results: They were found to be linear over a range of 12.5–37.5 μg ml-1 and 150–450 μg ml-1 for PREG and ETOR respectively. The retention time of PREG and ETOR was 3.523 min and 4.702 min, respectively. The mean percentage recoveries of PREG and ETOR were found to be 100.27% and 99.91%, respectively. The LOD was found 1.89 and 2.26 μg ml-1 and the LOQ were found 5.73 and 6.84 μg ml-1, for PREG and ETOR, respectively. Conclusion: This novel validated economical methods could be applicable for analysis of PREG and ETOR in pharmaceutical industries.
Keywords: Pregabalin; Etoricoxib; Method Validation; Simultaneous; ICH